МATHEMATICAL MODELING OF ETHANOL AND LACTIC ACID BIOSYNTHESIS BY THERMOPHILIC Geobacillus BACTERIA - M. A. Nuriddinov; F. V. Kazantsev; A. S. Rozanov; K. N. Kozlov; S. E. Peltek; I. R. Akberdin; N. A. Kolchanov (Вавиловский журнал генетики и селекции)
A mathematical model of the ethanol and lactic acid biosynthesis in the cells of Geobacillus spp. developed and adapted to the available experimental data is presented. It is shown that the mathematical model allows in silico design of genetic engineering experiments with the Geobacillus spp. bacterium and prediction of the dynamics of changes in synthesized ethanol and lactic acid concentrations depending on the molecular manipulations with the activity of enzymes of the metabolic system.